Pelatihan Strategi Pemasaran sebagai Upaya Meningkatkan Penjualan UMKM - Rika Sarfika; Mulyanti Roberto Muliantino; Luciana Luthan; Febi Sagitaria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Micro, Small and Medium Enterprises (MSMEs) are essential in economic development. The higher the MSMEs' income, the more the country's economy will increase. The ability to do marketing is needed to attract consumers, increase sales, maintain good relations with consumers, to advance MSMEs' income. However, due to limited knowledge, many MSMEs still need to be constrained by marketing, as experienced by Healthy Snacks